تعليم اللغة العربية بإستخدام طريقة لعبة البطاقة فى المدرسة الإبتدائية نور الجديد كروجيل مدينة بروبولنجو - Baidhowi, Idris; Ni’mah, Mamluatun; Sofa, Ainur Rofiq (ISLAMIKA, 2024)
This research explores the implementation of the Matching Card card game method in teaching Arabic at Madrasah Ibtidaiyah Nurul Jadid, Krucil, Probolinggo Regency, with the aim of improving students' Arabic language skills through an interactive and fun approach. This research method uses a descriptive qualitative approach with data collection in the form of observations and interviews regarding the Arabic language learning process in class 3. Researchers use Matching Cards containing pictures of vocabulary, phrases or sentences in Arabic, and their translations in Indonesian, in class. The results of the research show that the Matching Card card game method is effective in increasing students' understanding of Arabic vocabulary and structure. Students demonstrated high engagement and significant improvement in the ability to use Arabic in communicative situations. This method also increases students' learning motivation, creates a fun learning environment, and strengthens social interaction between students in the classroom.